1995
DOI: 10.1152/ajprenal.1995.268.6.f1185
|View full text |Cite
|
Sign up to set email alerts
|

Localization of dopamine D1A receptor protein in rat kidneys

Abstract: The dopamine D1A receptor subtype was identified in rat kidney with both light microscopic immunohistochemistry and electron microscopic immunocytochemistry. Antipeptide polyclonal antisera were directed to both extracellular and intracellular regions of the native receptor. The use of such receptor-subtype-selective antibodies allows for the identification of specific dopamine receptor subtype clones that are not distinguished by current pharmacological or receptor-ligand binding technology. Selectivity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 0 publications
6
61
0
Order By: Relevance
“…19,20 However, the kidney expresses DRD1 not only in the proximal tubules, but also in the medullary ascending limb of Henle, and in the medullary and cortical collecting ducts. 21,22 In the current study population, we previously demonstrated an inverse relation between RNa prox and mean arterial pressure. 9 In line with these findings, 9 the current analyses of the DRD1 haplotypes H1-AGC and H3-AAC showed opposite trends in blood pressure and RNA prox .…”
Section: Staessen Et Al Blood Pressure Sodium Handling Drd1 and Grk4supporting
confidence: 52%
“…19,20 However, the kidney expresses DRD1 not only in the proximal tubules, but also in the medullary ascending limb of Henle, and in the medullary and cortical collecting ducts. 21,22 In the current study population, we previously demonstrated an inverse relation between RNa prox and mean arterial pressure. 9 In line with these findings, 9 the current analyses of the DRD1 haplotypes H1-AGC and H3-AAC showed opposite trends in blood pressure and RNA prox .…”
Section: Staessen Et Al Blood Pressure Sodium Handling Drd1 and Grk4supporting
confidence: 52%
“…The specificity of this D 1 receptor antibody has also been reported. 19,29 Rat RPT cells were treated with vehicle (dH 2 O), angiotensin II or an AT 1 receptor antagonist (losartan) at the indicated concentrations and times. Immunoblotting was performed as previously reported, 22,26 except that the transblots were probed with the D 1 (1:800) or the AT 1 receptor antibody (1:400).…”
Section: Immunoblottingmentioning
confidence: 99%
“…10 D 2 -like receptors are also localised in the juxtaglomerular apparatus, the proximal and distal cortical tubules and CCD, in the renal vasculature adventitia, in the glomerulus and the terminal of the sympathetic nerves. [10][11][12] …”
Section: Receptors Localisation In Kidneysmentioning
confidence: 99%